Financial development convergence - Bahadir, Berrak; Valev, Neven (Journal of Banking & Finance, 2015)
We show that credit levels relative to GDP and other measures for financial development tend to converge across countries over time. The results are obtained using a broad sample of countries over many years and controlling for the quality of country-level institutions, the efficiency of financial institutions, and a range of macroeconomic variables. While we find evidence for convergence in the broad sample, we show that it levels off when countries reach a medium level of financial development. At high levels of financial development, convergence slows down even more and becomes negligible.